Immunological, anti-angiogenic and clinical effects of intratumoral interleukin 12 electrogene therapy combined with metronomic cyclophosphamide in dogs with spontaneous cancer: A pilot study. (1st August 2017) - Cicchelero, Laetitia; Denies, Sofie; Vanderperren, Katrien; Stock, Emmelie; Van Brantegem, Leen; de Rooster, Hilde; Sanders, Niek N.
Abstract: The immunological, anti-angiogenic and clinical effects of metronomic cyclophosphamide and 3 consecutive intratumoral interleukin (IL)-12 gene therapy (electrogene therapy (EGT)) treatments were evaluated in 6 dogs with spontaneous cancer. In all dogs, a decrease in peripheral leukocytes 2 days after IL-12 EGT coincided with erythema and swelling of the tumor. In the tumor, a transient increase in IL-12 levels was measured, whereas a continuous increase in interferon γ (IFNγ) and thrombospondin 1 (TSP-1) were determined in contrast to a continuous decrease in vascular endothelial growth factor (VEGF). In the serum, a transient increase in IL-12 and IL-10 levels were noted in contrast to a transient decrease in VEGF and TSP-1. The treatment resulted in a significant anti-angiogenic effect. Although all primary tumors continued to progress in time, this progression was slower than before treatment according to the contrast-enhanced ultrasound data. Besides the encouraging immunostimulatory and anti-angiogenic effects observed in all dogs we also noticed in 4 out of 6 dogs clinically relevant improvements in quality of life and weight. These results hold great promise for combinatorial strategies of IL-12 EGT and metronomic chemotherapy with conventional antitumor (immuno)therapies. Highlights: The combination of interleukin 12 and metronomic cyclophosphamide is safe and synergistic. IL-12-CP treatment induced an increased quality of life in dogs with spontaneous tumors. Despite primary tumor progression, clear anti-angiogenic effects were measured. IL-12-CP treatment induced pro-inflammatory changes in the tumor microenvironment.